Mechanosensing antagonizes ethylene signaling to promote root gravitropism in rice - Han-Qing Wang; Xing-Yu Zhao; Zhong Tang; Xin-Yuan Huang; Peng Wang; Wenhua Zhang; Yunhui Zhang; Sheng Luan; Fang-Jie Zhao (Nature Communications)
Abstract Root gravitropism relies on gravity perception by the root cap and requires tightly regulated phytohormone signaling. Here, we isolate a rice mutant that displays root coiling in hydroponics but normal gravitropic growth in soil. We identify COILING ROOT IN WATER 1 (CRW1) encoding an ETHYLENE-INSENSITIVE3 (EIN3)-BINDING F-BOX PROTEIN (OsEBF1) as the causative gene for the mutant phenotype. We show that the OsCRW1-EIN3 LIKE 1 and 2 (OsEIL1/2)-ETHYLENE RESPONSE FACTOR 82 (OsERF82) module controls the production of reactive oxygen species in the root tip, subsequently impacting root cap stability, polar localization of PIN-FORMED 2 (OsPIN2), symmetric distribution of auxin, and ultimately gravitropic growth of roots. The OsEIL1/2-OsERF82 ethylene signaling module is effectively impeded by applying gentle mechanical resistance to root tips, including growing in water-saturated paddy soil. We further show that mechanosensing-induced calcium signaling is required and sufficient for antagonizing the ethylene signaling pathway. This study has revealed previously unanticipated interplay among ethylene, auxin, and mechanosensing in the control of plant gravitropism.